PERANAN PEMERINTAH KELURAHAN DALAM MENINGKATKAN KUALITAS PELAYANAN PUBLIK - Sakira Achmad Alamri; Juriko Abdussamad; Romy Tantu (Kybernology Jurnal Ilmu Pemerintahan dan Administrasi Publik, 2024)
This study aims to explore the role of the urban village government in improving the quality of public services for the community, focusing on the following indicators: regulatory function, policy formulation, service delivery, law enforcement, and the maintenance of public order and security. This study uses a descriptive method with a qualitative approach. The data collection techniques include observation, interviews, and documentation. Data analysis involves data reduction, presentation, and conclusion drawing. The results indicate that the urban village governments in Talumolo and Leato Utara have performed various functions, but each function still faces several challenges which are noticeable from the following details: (1) The regulatory function in both urban villages is effective in creating a safe environment, but consistency and relevance of regulations sometimes pose challenges. (2) Policy formulation involves the participation of the community and stakeholders of both urban villages, despite concerns about the lack of community attention during the policy formulation process. (3) The service delivery function in both urban villages shows significant efforts, but there are several complaints about the effectiveness and efficiency of services. (4) Similarly, Law enforcement in Talumolo, which includes socialization and patrols, also has gotten several dissatisfaction complaints regarding the consistency of decisive actions, while in Leato Utara, training to reduce crime has not been effectively impactful. (5) The maintenance of public order is conducted through education and administrative services, but there are still concerns about compliance and service efficiency. Overall, even though progress has been made, improvements in consistency, relevance, and efficiency are still needed to achieve better outcomes.